História da participação do movimento indígena na constituição das 'escolas indígenas' no município de Santa Isabel do Rio Negro-AM - Pereira, Elio Fonseca (2010)
This research examines the history of Indigenous Movement's participation in the creation of indigenous schools in the municipality of Santa Isabel do Rio Negro - Amazonas - Brazil and teaching them the changes that occurred between the years 1990 to 2009, a period of transformation socio-political-cultural of the region. The research is based on the concepts of Indigenous Education School, Indigenous Movement, Intercultural Education and Curriculum. In the construction of a 'school of indigenous Indians "has been the conviction that the participation of the peoples in the process of setting up and running is essential. The study uses written documents (school records, decrees, ordinances, laws, reports of meetings) and social memory through interviews with a representative of religious institution and government, life history with teachers, parents and indigenous leaders. The research is of a qualitative analysis that examines the various sources concerning the history and socio-political-cultural city. The analysis is based on a historical perspective to the study of indigenous schools, highlighting the conflict and the different subjects who have participated in the creation and provision of school education in the relations between indigenous peoples and the institutional sectors involved